A single-unit design structure and gender differences in the swimming World Championships - Pushkar, S.; Issurin, V. B.; Verbitsky, O. (Journal of Human Kinetics, 2014)
Four 50 meter male/female finals - the freestyle, butterfly, breaststroke, and backstroke - swum during individual events at the Swimming World Championships (SWCs) can be defined in four clusters. The aim of the present study was to use a single-unit design structure, in which the swimmer was defined at only one scale, to evaluate gender differences in start reaction times among elite swimmers in 50 m events. The top six male and female swimmers in the finals of four swimming stroke final events in six SWCs were analyzed. An unpaired t-test was used. The p-values were evaluated using Neo-Fisherian significance assessments (Hurlbert and Lombardi, 2012). For the freestyle, gender differences in the start reaction times were positively identified for five of the six SWCs. For the backstroke, gender differences in the start reaction times could be dismissed for five of the six SWCs. For both the butterfly and breaststroke, gender differences in the start reaction times yielded inconsistent statistical differences. Pooling all swimmers together (df = 286) showed that an overall gender difference in the start reaction times could be positively identified: p = 0.00004. The contrast between the gender differences in start reaction times between the freestyle and backstroke may be associated with different types of gender adaptations to swimming performances. When the natural groupings of swimming stroke final events were ignored, sacrificial pseudoreplication occurred, which may lead to erroneous statistical differences.